Aplikasi Pembelajaran Pengenalan Nama Pahlawan Menggunakan Algoritma Fisher-Yates - Muhammad Aldito Ardiansyah; R. M. Nasrul Halim (SMATIKA JURNAL : STIKI Informatika Jurnal, 2024)
Application of technology in learning activities is the right decision, because most children have a great sense of curiosity, such as curiosity about heroes. Heroes are historical figures who contribute to the development of nations and countries. A use of technology that can be used is a learning application and is generally made in the form of quiz games. Quiz games are games that are played by answering existing questions. The questions were randomly selected using the Fisher-Yates algorithm. The Fisher-Yates algorithm is a calculation by creating random variations of existing sets. The Multimedia Development Life Cycle method is employed in this research as it is suitable for building multimedia application systems. In this development, the test stage uses the black box testing method. Based on the research results and the development process, it can be concluded that the application of the Fisher-Yates algorithm can run well in randomizing questions based on the results of 15 trial tests. And according to the black box testing results, it indicates that the created application can be used properly.